Modelling and thermal analysis of micro beam using comsol multiphysics - Ülkir, Osman; Ertuğrul, İshak; Girit, Oğuz; Ersoy, Sezgin (Serbian Society of Heat Transfer Engineers, 2021)
In this study, the design and analysis of the micro beam is carried out using COMSOL multiphysics. The current passing through the beam distributes the heat energy due to its resistance that pushes the entire micro beam to the desired distance through thermal expansion. This expansion varies depending on the amount of current passing through the beam and the emitted temperature. The purpose of the model created is to estimate the amount of current and temperature increase required to cause displacement in the proposed micro beam using analysis software. In addition, displacements and temperature data produced in micro beams for different metallic materials (Al, Cu, Ni, and Pt) and different input potentials (0.3 V, 0.6 V, and 0.9 V) are reported. These materials are used as functional materials in the field of micro-electro-mechanical-system because of their important physical and electrical properties. As a result of the simulation studies, increasing the voltage increased the displacement in the materials and the resulting temperature. While there is a serious difference between the displacement data of the materials, the temperatures are close to each other. When 0.9 V voltage is applied, the highest displacement values for Al, Cu, Ni, and Pt are; 7.88 ?m, 5.36 ?m, 3.62 ?m, and 2.72 ?m, respectively. As a result, it has been observed that aluminum used in micro beam design gives a significant amount of displacement for the proposed geometry when compared to other metallic beams. © 2021 Society of Thermal Engineers of Serbia Published by the Vin?a Institute of Nuclear Sciences, Belgrade, Serbia. This is an open access article distributed under the CC BY-NC-ND 4.0 terms and conditions
2-s2.0-85101696135
Keywords: COMSOL multiphysics; displacement; electrical potentia; micro beam; thermal expansion